Gamma-radiation-induced DNA damage and repair in human peripheral lymphocyte subpopulations as studied by nucleoid sedimentation - Jansen van Rensburg, Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1987.